Experimental study on an SI engine fuelled by gasoline/acetylene mixtures. (15th May 2018) - İlhak, Mehmet İlhan and Akansu, Selahaddin Orhan and Kahraman, Nafiz and Ünalan, Sebahattin
Abstract: Internal combustion engines that are widely used as a power source in passenger and freight transport, individual transport vehicles, agricultural sector, fixed and mobile generators, are dependent on fossil fuels, especially oil. However, decrease in the oil reserves and environmental problems such as the global warming have compelled researchers to search for alternative fuels for internal combustion engines. In this study, the effects of the use of gasoline and acetylene mixtures on the overall performance of a spark ignition (SI) engine have been experimentally investigated. Experiments have been carried out on a four-stroke, four-cylinder, water-cooled SI engine and at stoichiometric conditions. Acetylene flow rates were fixed at 500 g/h and 1000 g/h in these experiments. The performance and emission parameters were studied by changing the load from 25% to the full load. The maximum acetylene content of the gasoline-acetylene mixture was 54% at 25% load, while this rate was 22.4% at the full load. Acetylene induction resulted in lower thermal efficiency at almost all loads. A decrease in hydrocarbon emissions was observed at all engine loads while NO emissions increased at low loads when compared to that of gasoline.